2021
DOI: 10.3390/met11020334
|View full text |Cite
|
Sign up to set email alerts
|

Assessment the Partial Welding Influences on Fatigue Life of S700MC Steel Fillet Welds

Abstract: Fine-grained steels belonging to the HSLA group (High-Strength Low-Alloy steels) of steels are becoming increasingly popular and are used in both statically and dynamically stressed structures. Due to the method of their production, and thus also the method use to obtain the required mechanical properties, it is really necessary to limit the heat input values for these steels during welding. When applying temperature cycles, HSLA steels in highly heated heat-affected zones (HAZ) reveal intensive grain coarseni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This inferior performance under certain load conditions, shown by electrodes with high levels of alloying elements like the ER110S-G and ER120S-G electrodes, can be attributed to the geometric condition of the weld bead edge, which may result in potential geometric defects that enhance stress concentration in this region. Studies by Moravec et al [15] and Rariprasath et al [35] report the effect of stress concentrators at the edges of weld beads on the fatigue life of HSLA steels, indicating that these points are severe stress concentrators due to the margin geometry. Along with the microstructural changes caused by heat in the Heat-Affected Zone (HAZ) that lead to local hardness reduction, these factors facilitate the initiation and propagation of cracks under cyclic loads.…”
Section: Fatigue Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…This inferior performance under certain load conditions, shown by electrodes with high levels of alloying elements like the ER110S-G and ER120S-G electrodes, can be attributed to the geometric condition of the weld bead edge, which may result in potential geometric defects that enhance stress concentration in this region. Studies by Moravec et al [15] and Rariprasath et al [35] report the effect of stress concentrators at the edges of weld beads on the fatigue life of HSLA steels, indicating that these points are severe stress concentrators due to the margin geometry. Along with the microstructural changes caused by heat in the Heat-Affected Zone (HAZ) that lead to local hardness reduction, these factors facilitate the initiation and propagation of cracks under cyclic loads.…”
Section: Fatigue Testsmentioning
confidence: 99%
“…A region of lower hardness does not always indicate a reduction in the static strength of welded joints. The area of this low-hardness region and the alloying elements present in the welding consumables can ensure the mechanical strength in this region, even with microstructural modifications [12][13][14][15][16][17]. The region of lower strength in welded joints is typically in the recrystallized region of the heat-affected zone.…”
Section: Introductionmentioning
confidence: 99%
“…Among the PERFORM steels, PERFORM 700, which is also known as S700MC, is one of the most employed steel grades [10]. Due to its popularity, much work has been done on welding similar and dissimilar joints [11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…They reported a limited reduction in the yield strength since most of the plastic deformation is formed in both the heat-affected and fusion zones. Moravec et al [15] studied the fatigue life performance of MAG-welded S700MC. They reported that the application of the double-sided fillets adversely influenced fatigue life.…”
Section: Introductionmentioning
confidence: 99%
“…Special metallurgical attention is given to the weld region [15,16]. Controlling the heat input during welding to maintain the mechanical properties is of special importance for fine-grained high-strength steels [17]. The selection of appropriate electrode material is of high importance [18,19].…”
Section: Introductionmentioning
confidence: 99%